UPAYA MENINGKATKAN HASIL BELAJAR FIKIH MATERI SHALAT JENAZAH MELALUI METODE SMALL GROUP DISCUSSION DAN PRAKTIK UNJUK KERJA PADA SISWA KELAS X KA MAN 2 KOTA CILEGON - JUPRI JUPRI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve the learning outcomes of Jurisprudence on the material for funeral prayer in class X KA semester 1 MAN 2 Cilegon City in the 2021/2022 academic year through the application of the Small Group Discussion (SGD) cooperative learning method and performance practices. The research was carried out at MAN 2 Kota Cilegon with the research subjects of all students of class X KA semester 1 MAN 2 Cilegon City for the 2021/2022 academic year, totaling 36 students. The research method uses Classroom Action Research. Data was collected through observation, documentation and tests. Data analysis was carried out in 3 (three) stages including: data reduction, data presentation and conclusion drawing or verification. The hypothesis states that it is suspected that through the application of the Small Group Discussion (SGD) cooperative learning method and performance practices, it can improve Fiqh learning outcomes for the funeral prayer material in class X KA semester 1 MAN 2 Cilegon City for the 2021/2022 academic year. Empirical data from research results state that through the application of the Small Group Discussion (SGD) cooperative learning method and performance practices can improve Fiqh learning outcomes for the funeral prayer material for X KA students in semester 1 of MAN 2 Cilegon City in the 2022/2023 academic year. From the initial conditions the average value of student learning outcomes in Fiqh is only 67 with learning completeness of 47.5% (19 students), in the first cycle the average value becomes 72 with learning completeness of 65.0% (26 students), and in the second cycle the average value Fiqh learning outcomes of students became 79 with a learning completeness of 90.0% (36 students). The conclusion of the study is that through the application of the Small Group Discussion (SGD) cooperative learning method and performance practices can improve Fiqh learning outcomes for the funeral prayer material in class X KA semester 1 MAN 2 Cilegon City for the 2021/2022 academic year. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar Fikih materi shalat jenazah pada siswa kelas X KA semester 1 MAN 2 Kota Cilegon Tahun Pelajaran 2021/2022 melalui penerapan metode pembelajaran kooperatif Small Group Discussion (SGD) dan praktik unjuk kerja. Penelitian dilaksanakan di MAN 2 Kota Cilegon dengan subjek penelitian seluruh siswa kelas X KA semester 1 MAN 2 Kota Cilegon Tahun Pelajaran 2021/2022 yang berjumlah 36 siswa. Metode penelitian menggunakan Penelitian Tindakan Kelas. Pengumpulan data dilakukan melalui observasi, dokumentasi dan tes. Analisis data dilakukan dengan 3 (tiga) tahapan meliputi: reduksi data, penyajian data dan penarikan kesimpulan atau verifikasi. Hipotesis menyatakan diduga melalui penerapan metode pembelajaran kooperatif Small Group Discussion (SGD) dan praktik unjuk kerja dapat meningkatkan hasil belajar Fikih materi shalat jenazah pada siswa kelas X KA semester 1 MAN 2 Kota Cilegon Tahun Pelajaran 2021/2022. Data empiris hasil penelitian menyatakan bahwa melalui penerapan metode pembelajaran kooperatif Small Group Discussion (SGD) dan praktik unjuk kerja dapat meningkatkan hasil belajar Fikih materi shalat jenazah pada siswa X KA semester 1 MAN 2 Kota Cilegon Tahun Pelajaran 2022/2023. Dari kondisi awal nilai rata-rata hasil belajar Fikih siswa hanya 67 dengan ketuntasan belajar 47.5% (19 siswa), pada siklus I nilai rata-rata menjadi 72 dengan ketuntasan belajar 65.0% (26 siswa), dan pada siklus II nilai rata-rata hasil belajar Fikih siswa menjadi 79 dengan ketuntasan belajar 90.0% (36 siswa). Simpulan penelitian adalah melalui penerapan metode pembelajaran kooperatif Small Group Discussion (SGD) dan praktik unjuk kerja dapat meningkatkan hasil belajar Fikih materi shalat jenazah pada siswa kelas X KA semester 1 MAN 2 Kota Cilegon Tahun Pelajaran 2021/2022